REVISITING IMPOVERISHMENT: ISSUES IN THE EPOCH OF EXPANDING GLOBAL TRADE TARIFFS - Ang, Siew Mun (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Poverty or impoverishment is a multidimensional issue which can cause social disruption if the poor are neglected. It is then unsurprising that countries around the world are concerned about alleviating poverty. Therefore, the United Nations’ 17 Sustainable Development Goals (SDGs) has ‘No Poverty’ as its first goal because all poor men, women and children experience well-being and mental health issues as well as general deprivation in accessing goods and services. As a microcosm of the world at large, Malaysia has been committed to overcoming poverty with successes for the past 40 years. For example, its absolute poverty rates declined from 20.7% (1984) to 0.4% (2016) only for it to surge again to 6.2% (2022) after the Covid-19 pandemic (OpenDOSM, 2023). Similarly, world poverty rates rose after the pandemic (The World Bank, 2022), reviving old challenges. Moreover, on 2nd April 2025, a new epoch of global trade protectionism began with the United States (US) announcing a 10% baseline tariff on all its trading partners and reciprocal tariffs on certain countries. Will this situation affect all impacted countries’ economy, their prosperity and their poor? Will these poor be disproportionately affected more, just like how climate change and the Covid-19 pandemic have already adversely impacted them? In this preliminary paper, I have outlined a two-pronged goal: (1) to revisit poverty by outlining possible issues faced by the poor in this new epoch of global trade tariffs and (2) to briefly explore possible solutions to poverty. Methodologically, this paper is based on secondary research of existing literature. Finally, Gemini and DeepSeek, the two artificial intelligence (AI) chatbots, were used for brainstorming.